Um estudo comparativo entre o PNQ e as NBR ISO 9000, NBR ISO 14000 e OHSAS 18001, como instrumento de administração estratégica - Santos, Vania Sant\'anna (2002)
This research approaches various International Quality Awards, as following: Australian, Canadian, Japanese (Deming Prize), European, American (Malcoim Baidrige Award) and Mexican, National Quality Award and the International Norm series 9000:2000 Quality Managcmcnt Systcm, ISO 14000:1996 Environmcntal Managcmcnt Systcm and OHSAS 18001:1999 Occupational Health and Safety Assessment Series. This objectives of the research is a comparative study between the Brazilian National Quality Award, International Quality Awards and the Norms above-mentioned. The modeis of management system, the principies and respective definitions are analyzed. Afier, the similarities and spccffics charactcristics arc invcstigatcd bctwccn thc norms and National Quality Awards,. An outline of the professionais and the organizations that are actuating in each types of rnanagement system are presented. Tt is suggested a conceptual model of management integrated system of quality, environmcntal and occupational health and safety based in thc exceilence principies of NQA to be utiized in organizations that search excelience management.